Valorisation of Teucrium montanum as a Source of Valuable Natural Compounds: Bioactive Content, Antimicrobial and Biological Activity – A Review - Šeremet, Danijela; Cebin, Aleksandra Vojvodić; Mandura, Ana; Komes, Draženka (Pharmacognosy Reviews)
One of the most popular species among Teucrium genus, T. montanum has been used as medical herb for generations, but first scientific investigations regarding its bioactive content date back only a few decades ago. Today is known that T. montanum is rich in flavonoids and phenolic acids, secondary metabolites with high antioxidant activity and yields relatively high content of essential oil rich in sesquiterpenoids. Most of the published papers investigating T. montanum are focused on the characterization of its essential oil that is summarised in the present review paper together with less investigated phenolic content and biological activity resulting from the presence of bioactive compounds.
Keywords: Bioactive compounds; Biological activity; Medical herb; Phenolic compounds; Teucrium montanum